JITU (Fish Pinch Catch Profit) Surronding Net Increases Male Mackerel Catch in Siofabanua Village, North Nias - ZEGA, ASOKHIWA; Gea, Angel Sri Ayu (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2024)
This study aimed to evaluate the effectiveness of using surround nets in increasing the catch of male mackerel in Siofabanua Village, North Nias Regency. In an effort to overcome the low catch of conventional methods, this study investigated the technical and environmental factors that influence the success of surround nets. The research method used a descriptive qualitative approach with field observations, in-depth interviews with fishermen, as well as the study of relevant documents. The results showed that the use of circle nets significantly increased the number and quality of catches, as well as the time and labor efficiency of fishers. The main factors influencing the successful use of circle nets are the condition of the net, placement techniques, and environmental factors such as water depth, food sources, and underwater habitat structure around Siofabanua Village. In addition, weather and seasonal factors also impact catch success. Recommendations include improving net specifications, providing technical training to fishers, and developing policies and regulations that support sustainable fisheries. In conclusion, the use of circle nets has the potential to be an effective and environmentally friendly technology in increasing the productivity of local fisheries in Siofabanua Village, as well as supporting sustainable fisheries practices and marine resource conservation